2002
DOI: 10.1021/ac0109467
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Fritless Column for On-Chip Capillary Electrochromatography with Conventional Stationary Phases

Abstract: A new polymer device for use with conventional particulate stationary phases for on-chip, fritless, capillary electrochromatography (CEC) has been realized. The structure includes an injector and a tapered column in which the particles of the stationary phase are retained and stabilized. The chips were easily fabricated in poly-(dimethylsiloxane) using deep-reactive-ion-etched silicon masters, and tested using a capillary electrophoretic separation of FITC-labeled amino acids. To perform CEC, the separation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 103 publications
4
101
0
Order By: Relevance
“…Next, the designed channel patterns were transferred to silicon wafers using a mask aligner (ES 20, Nanometric Technology, Inc., Japan). After developing in ethyl lactate (Wako Pure Chemical Ind., Osaka, Japan), the surface of masters were treated with dimethyloctadecylchlorosilane 23 (Shin-Etsu Chem. Co., Japan) for the easy peeling off of a PDMS replica.…”
Section: Preparation Of Replica Mastersmentioning
confidence: 99%
“…Next, the designed channel patterns were transferred to silicon wafers using a mask aligner (ES 20, Nanometric Technology, Inc., Japan). After developing in ethyl lactate (Wako Pure Chemical Ind., Osaka, Japan), the surface of masters were treated with dimethyloctadecylchlorosilane 23 (Shin-Etsu Chem. Co., Japan) for the easy peeling off of a PDMS replica.…”
Section: Preparation Of Replica Mastersmentioning
confidence: 99%
“…Since the first realization of -TAS by Manz et al [3] in 1990, this approach has caused a profound revolution in the conception of analytical instrumentation. Many studies [4][5][6][7] have been made in this field, and it had been shown to offer enormous practical potential in chemical and biochemical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Silica aerogels hold records for the lowest However, only a few chip-based chromatographic systems have 50 been reported so far as compared to chip-based capillary elec-51 trophoretic (CE) devices, which is mainly due to technical problems 52 inherent in the former [7,8]. Most microfluidic devices are based on 53 open tubular flow designs and only a few involve packed-bed chips 54 due to the difficulty in preparing frits [9,10]. Recently, this prob-55 lem has been excellently addressed [11], however, the high-tech 56 manufacturing of the three-laminated polyimide layers chip (use 57 of laser, micromachined frit) is not possible for the large majority 58 of the researchers.…”
mentioning
confidence: 99%
“…The packing was prepared daily, and it was preconditioned with that it was only necessary to taper a rigid capillary [9] or flexible 157 microfluidic channel [12] to approximately 10 m (inner diameter) 158 to achieve the keystone effect [9] and to retain 3 m sized particles. It…”
mentioning
confidence: 99%